The Potential Use of Entomopathogenic Nematodes to Control Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae) - le Vieux, P.D.; Malan, A.P. (South African Journal of Enology and Viticulture, 2013)
Laboratory bioassays were conducted to establish the potential of entomopathogenic nematodes (EPNs) as biocontrol agents of Planococcus ficus (Signoret). Six indigenous and two commercially available nematode species were screened for their efficacy in killing adult female P. ficus. The two indigenous species with the most promising results were Heterorhabditis zealandica and Steinernema yirgalemense, which were responsible for 96% and 65% mortality respectively. Tests were conducted to compare the efficacy of H. bacteriophora and S. feltiae produced in vivo and in vitro. Heterorhabditis bacteriophora showed no significant difference in efficacy between the two production methods, but in vivo-cultured S. feltiae produced a significantly higher mean mortality of 40%, in contrast to a 19% mean mortality with in vitroproduced infective juveniles (IJs). The capability of both H. zealandica and S. yirgalemense to complete their life cycles in the host and to produce a new cohort of IJs was demonstrated. Bioassays indicated a concentration-dependent susceptibility of P. ficus to H. zealandica, S. yirgalemense and commercially produced H. bacteriophora, with LC50 and LC90 values of 19, 82; 13, 80; and 36, 555 respectively. Both H. zealandica and S. yirgalemense were able to move 15 cm vertically downward and infect P. ficus with a respective mortality of 82% and 95%. This study showed P. ficus to be a suitable host for H. zealandica and S. yirgalemense, with both nematode species showing considerable potential for future use in the field control of P. ficus.